Establishment and evaluation of a simulated high-altitude hypoxic brain injury model in SD rats - Hou, Ya (Mol Med Rep, 2019)
This study was conducted to establish a stable hypobaric hypoxia brain injury model. SD rats were randomly separated into control and model groups, and placed outside or inside of a hypobaric chamber, respectively. Subsequent to 24 h anoxic exposure, plasma superoxide dismutase (SOD), malondialdehyde (MDA), glutathione (GSH), oxidized glutathione (GSSG) and lactate dehydrogenase (LDH) were measured using commercial biochemical kits. Hematoxylin-eosin (H&E), Nissl's and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining were used to observe the morphology of neurons in the hippocampus. The protein expression levels of apoptotic protease activating factor-1 (Apaf-1), hypoxia inducible factor-1α (HIF-1α), caspase-3, cleaved caspase-3, Bcl-2-associated X protein (Bax) and cytochrome c (cyto-c) were detected using western blot and immunohistochemistry analyses. Hypoxic substantially induced morphological lesions in the hippocampus concomitant with the physical behavioral performance deficit. Furthermore, hypoxia markedly exacerbated the levels of MDA, LDH and GSSG, and restrained GSH (P<0.01) and SOD (P<0.05) levels compared with the control group. In addition, hypoxia significantly induced the protein expression of Apaf-1, HIF-1α, caspase-3, cleaved caspase-3, Bax and Cyto-c (P<0.01) compared with the control group. Finally, a lower number and volume of Nissl bodies were verified in the hypoxic group. TUNEL results demonstrated a greater number of apoptotic cells in the hypoxic group. The present study demonstrates a model of rat hypoxic brain injuries induced by a hypobaric chamber at 9,000 m for 24 h. Furthermore, the redox enzyme, HIF-1α and mitochondrial apoptosis-associated protein, along with H&E and Nissl's staining, may be applied to evaluate the degree of injury.